Pembentukan Karakter Islami Melalui Kegiatan Muhadharah di PP. Al-Ma’ruf Sidokumpul Lamongan - Moch Faizin Muflich; Idham Cholid Syazili (Akademika, 2023)
Character building is increasingly being explored for potential development solutions for Indonesian educational standards. because so far the education system is considered unsuccessful because of school graduates with intelligent minds who are skilled but mentally fragile. The problems in this study are (1) How muhadharah activities in PP. Al-Ma'ruf Sidokumpul Lamongan? (2) What Islamic character is formed through the activities of Muhadharah in PP. Al-Ma'ruf sidokumpul Lamongan?, the approach in this study is qualitative, the findings show that the process of forming Islamic characters in pp. al-ma'ruf with three phases: Knowledge, Implementation and Habituation.  And the quality of character produced from muhadharah activities in PP. Al-Ma'ruf is Confident, Responsible, and Brave.